Where are all the anthelmintics? Challenges and opportunities on the path to new anthelmintics. (December 2020) - Nixon, Samantha A.; Welz, Claudia; Woods, Debra J.; Costa-Junior, Livio; Zamanian, Mostafa; Martin, Richard J.
Abstract: Control of helminth parasites is a key challenge for human and veterinary medicine. In the absence of effective vaccines and adequate sanitation, prophylaxis and treatment commonly rely upon anthelmintics. There are concerns about the development of drug resistance, side-effects, lack of efficacy and cost-effectiveness that drive the need for new classes of anthelmintics. Despite this need, only three new drug classes have reached the animal market since 2000 and no new classes of anthelmintic have been approved for human use. So where are all the anthelmintics? What are the barriers to anthelmintic discovery, and what emerging opportunities can be used to address this? This was a discussion group focus at the 2019 8th Consortium for Anthelmintic Resistance and Susceptibility (CARS) in Wisconsin, USA. Here we report the findings of the group in the broader context of the human and veterinary anthelmintic discovery pipeline, highlighting challenges unique to antiparasitic drug discovery. We comment on why the development of novel anthelmintics has been so rare. Further, we discuss potential opportunities for drug development moving into the 21st Century. Graphical abstract: key challenges and opportunities identified by the 2019 CARS meeting for anthelmintic discovery in the context of the overall drug development process. Image 1